Acoustic emission signal analysis during chip formation process in high speed machining of 7050-T7451 aluminum alloy and Inconel 718 superalloy. (June 2017) - Wang, Bing; Liu, Zhanqiang
Graphical abstract: Highlights: Relationship between acoustic emission (AE) signal and chip morphology is revealed. Time and frequency domain characteristics of AE signals are analyzed. Chip serrated frequencies are equal to the corresponding AE dominant frequencies. AE root mean square values are affected by the cutting energy in machining process. Abstract: Research on acoustic emission (AE) signal during chip formation process in high speed machining can help to reveal the workpiece-chip material separation mechanism. The aim of this paper is to explore the relationship between the AE signal with chip formation and cutting energy consumption. Firstly, the high speed orthogonal cutting experiments of 7050-T7451 aluminum alloy and Inconel 718 are carried out with the cutting speed ranging from 50 m/min to 8000 m/min, during which the AE signals are detected. Then the micrographs of chip morphology under different cutting speeds are collected and observed. The results show that dimples and ductile fracture are observed on the serrated chip free surface, which are caused both by adiabatic shear and severe plastic deformation, while brittle fracture is the mechanism for fragmented chip formation. All these deformation features are demonstrated to be the sources for AE signals generation. The time and frequency domain characteristics of detected AE signals during high speed machining of the two workpiece materials are analyzed. The chip serrated frequencies for the two workpiece materials during high speed machining are found to be nearly equal to their corresponding AE dominant frequencies. It confirms that the procedure of serrated chip formation makes a significant contribution to the produced AE signal. The dependence of AE root mean square (RMS) values on specific cutting energy during high speed machining has also been revealed. The material deformation and subsequent release of strain energy prove to be dependent on the conditional ductile and brittle mechanical properties of the machined material.